Multiple particle and cluster emissions from Zr following intermediate energies photo absorption - Rodrigues, T. E.; Martins, M. N.; Arruda-Neto, J. D T; Mesa, J.; Garcia, C.; Shtejer, K.; Garcia, F. (My University, 2007)
A new approach based on a N-a cluster photoabsorption model is proposed for the understanding of the puzzling steady increase behavior of the 90Zr (e, α) yield measured at the National Bureau of Standards (NBS) within the Giant Dipole Resonance and quasideuteron energy range. The calculation takes into account the pre-equilibrium emissions of protons, neutrons and alpha particles in the framework of an extended version of the multicollisional intranuclear cascade model (MCMC). Another Monte Carlo based algorithm describes the statistical decay of the compound nucleus in terms of the competition between particle evaporation (p, n, d, α, 3He and t) and nuclear fission. The results reproduce quite successfully the 90Zr (e,α) yield, suggesting that emissions of a particles are essential for the interpretation of the exotic increase of the cross sections.
Keywords: Atoms; Helium; Compound nucleuses; Cross sections; Energy ranges; Extended versions; Intermediate energies; Intranuclear cascade models; Monte carlo; Multiple particles; New approaches; Photoabsorption; Zirconium